(untitled) (Global Journals of Research in Engineering, 2023)
Through Monte Carlo simulations and a break-even analysis this study monetizes the rising costs of orbital debris and space preservation This study estimates the costs of allowing space debris to persist and proliferate using existing data and projections from the literature This study assigns values to NASA s published space debris mitigation models to calculate the costs of space preservation Estimating the costs of space debris has been hampered by a lack of information owing primarily to commercial proprietary information This study demonstrates how simple-realistic assumptions can transform sparse data into the foundation of a robust analysis Furthermore by conducting a break-even analysis of these costs based on defining quantitative variables in models this study identifies the global cost savings and the likely timeline when the costs of space debris will equal the costs of space preservation This study uses sensitivity analysis with alternative inputs to identify uncertainties in the costs of orbital debris and space preservation